A trauma informed response to COVID 19 and the deteriorating mental health of refugees and asylum seekers with insecure status in Australia. (10th September 2021) - Kenny, Mary Anne; Grech, Carol; Procter, Nicholas
Abstract: COVID‐19 brings increased risk to the mental health of asylum seekers and refugees in Australia on temporary visas. Rapid government changes due to the COVID‐19 pandemic are resulting in significant and sustained hardship on this already vulnerable group. This discursive paper is both an explainer and a resource for mental health nurses and health professionals with scope of practice in primary care and emergency departments responding to this population. The aim of this paper is to alert clinicians to the drivers of mental and suicide related distress and to provide recommendations as to how to therapeutically engage and support this group. Drivers include complex intersections between legal uncertainty, economic, social and mental health stress as drivers of entrapment, acute mental distress and suicidal ideation. Information about the COVID‐19 related factors as drivers contributing to worsening states of distress may help guide clinicians to consider protective factors designed to mitigate the onset or worsening of mental distress, plus aid in the development of health policy and service‐delivery arrangements of support and therapeutic engagement.